Im/materialities - Zoë Crossland; Alexander Bauer (Semiotic Review, 2017)
There has been a sustained and forceful call in recent anthropological accounts to engage more critically with the tangible materiality of the world, and especially a demand to take into account the ability of things to resist or exceed the discursive frameworks within which humans situate them. In this shift away from questions of subjectivity and interpretation, there is often an attendant downplaying of the semiotic. We resist this dualistic framing of semiotics in opposition to material things, and suggest that we should think more carefully about the assumption that subjectivity, interpretation and semiotics should be pushed aside in order to explore the nonhuman. Here we construe semiotics more broadly, recognizing a more encompassing field that engages explicitly with the non-representational, drawing upon a Peircean heritage. Rather than putting questions of representation to one side in order to focus on the peculiar characteristics of things, in this issue we situate representation within a wide-ranging field of sign-making and sign-perception, in which the concrete characteristics and qualities of sign relations are fully recognized. This is to put representation in its place as one of many forms of sign-relation, and similarly to situate human ways of knowing within a world of knowing actors, humans and nonhumans alike.